SPEECH ACT AS AN IMPORTANT FUNCTION OF COMMUNICATION (Scientific journal of the Fergana State University, 2024)
Speech acts are important part of communication as we perform it when we offer an apology, greetings, request, complains, compliment and refusals. The author illustrates the idiosyncrasies of speech act analyzing different points of view of famous linguists.